Homeowners' Perceptions of Seismic Building Performance and Implications for Preparedness in New Zealand - Miranda C; Becker JS; Toma CL; Vinnell LJ (American Society of Civil Engineers, 2023)
Over the last decade, engineering studies have mentioned the need for meeting societal demands of damage expectations and housing performance for major earthquakes. However, they do not refer to any systematic analysis examining such societal demands, nor have they investigated interactions of this with voluntary seismic strengthening. A questionnaire distributed to homeowners of wooden-framed houses in the Wellington region of New Zealand investigated these issues. Survey respondents expected a better seismic performance of their house after voluntarily undertaking structural strengthening (i.e., positive outcome expectancy) and expected a better seismic performance of their house, regardless of the use of strengthening, than what is accepted by current seismic codes, which aim for life safety (i.e., collapse prevention). Although this study found that experience of damage in past earthquakes was not associated with final implementation of such preparedness measures, access to strengthening information and trust toward providers of information, such as builders, were found to play a key role when adopting strengthening. This study gives insight into the role that outcome expectancy and sources of information play in voluntary structural strengthening of residential low-rise buildings and indicates a need for better engagement, such as working closer with builders as sources of information, to reduce losses in future major earthquakes.
(c) The Author/s